Mengoptimalisasi Peran PMO (Pengawasan Menelan Obat) Dalam Kepatuhan Minum Obat Pada Pasien TBC - Santi Elvira; Asti Vebriyanti Asjur; Syaifullah Saputro; Tamzil Azizi Musdar; Wahyu Nuraini Hasmar (Jurnal Informasi Pengabdian Masyarakat, 2023)
Tuberculosis is a disease caused by Microbacterium tuberculosis and is a major cause of disability and death in most countries around the world. Tuberculosis is still a health problem for people in the world. The World Health Organization (WHO) in 2018 stated that there were 10 million cases of TB with 1,2 million died due to HIV negative and 251.000 died due to HIV positive with TB complications, around 44% of these patients were in the southeast asia region. In 2021 the prevalence of TB is estimated to reach 10,6 million cases, with 6 million cases in man, 3,4 million cases in women and the rest are children. The causes of failure of TB patients are non-adherence to taking medication and resistance to treatment. One of the efforts in treating TB for the cured category is monitoring drug swallowing (PMO). The role of a PMO it self is to supervise taking medication regularly until the end of treatment, to encourage patients to want to take medication regularly, and to provide counseling to family members of patients if they have symptoms that lead to TB disease. There are several factors that play an important role in family motivation and PMO are family background factors such as education, environmental conditions and socio-economic conditions.